Expression of Leptin, Leptin Receptor, Adiponectin, and Adiponectin Receptor in Ductal Carcinoma In Situ and Invasive Breast Cancer - Jeong, Young-Ju (Korean Breast Cancer Society, 2011)
PURPOSE: Adipocytokines, such as leptin, resistin, and adiponectin, are associated with obesity and breast cancer. Several studies have indicated that adipocytokines may influence tumor growth or differentiation. The aims of this study were to determine the expression of leptin, leptin receptor (ObR), adiponectin and adiponectin receptor (AdipoR) in human breast cancer, to evaluate their prognostic significance in the breast cancer. METHODS: Specimens from 198 patients with primary breast cancer were enrolled, and representative paraffin tumor blocks were selected for constructing tissue microarrarys (TMA). Immunohistochemical staining for leptin, ObR, adiponectin, and AdipoR was performed using TMA, and the clinicopathologic characteristics were evaluated from the patient's medical records. RESULTS: Stage 0 breast cancer accounted for 41 cases, and 157 cases were invasive cancer. Positive rates of leptin and ObR expression in the ductal carcinoma in situ (DCIS) group were significantly higher than those of the invasive cancer group (97.4% vs. 34.0%, p<0.001; 74.4% vs. 29.8%, p<0.001). However, positive rates of adiponectin and AdipoR expression in the invasive cancer group were significantly higher than those in the DCIS group (53.7% vs. 33.3%, p=0.024; 59.9% vs. 26.3%, p<0.001). High leptin expression was significantly associated with high Ki-67 expression (p=0.016). High adiponectin expression was significantly correlated with smaller tumor size (p=0.001). CONCLUSION: We suggest that losses of leptin and ObR expression could be associated with invasive cancer, whereas high adiponectin and AdipoR expression may be associated with breast cancer invasiveness.